NILAI-NILAI BUDAYA DALAM UPACARA NENI URAN WAIR PADA MASYARAKAT TANAH AI DI KABUPATEN SIKKA NUSATENGARA TIMUR - Gustav Gisela Nuwa; Maria R. Aquinoranda (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2020)
Cultural issues are the ones often discussed today, especially in the effort to preserve them. In the Tanah Ai community, it is very important to maintain ancestral heritage in the Neni Uran Wair ceremony. This research was conducted in Sikka Regency, East Nusa Tenggara, Tanah Ai Tribe. This study aims to determine the values contained in the Neni Uran Wair ceremony and the effort to preserve cultural values ​​in the Neni Uran Wair ceremony. In this study, researchers used qualitative methods using ethnographic methods. The data sources in this research were primary data and secondary data. Primary data included customary leaders, community leaders and youth, while secondary data included documents and photos of documentation. The techniques of collecting data used in this study were observation, interviews, and documentation. Meanwhile, data analysis technique included data collection, data education, data presentation and data verification. The results showed that the values ​​contained in the Neni Uran Wair ceremony were religious, cooperation values, brotherhood values, social values, and economic values. Meanwhile, the conservation efforts includes the involvement of the local government and the young generation by forming a customary group and location (Nuba and Mahe), and cultural revitalization.